MANAJEMEN SUPERVISI KLINIS KEPALA MADRASAH DALAM PENINGKATAN PROFESIONALITAS GURU DI MTs MAMBA’UL HISAN SIDAYU GRESIK - Fahruddin, Ahmad Afghor; Warti’ah, Warti’ah; Supriyanto, Supriyanto (Attaqwa: Jurnal Ilmu Pendidikan Islam, 2024)
Clinical supervision is an improvement activity in learning through systematic stages starting from planning, observation, and analysis of learning activities with the aim of enhancing the learning process. The method used in this research employs a qualitative descriptive research approach with data collection techniques including observation, interviews, and documentation. Data analysis is conducted by Miles and Huberman, and data validity refers to four validation standards consisting of Credibility, Transferability, Dependability, and Confirmability. The Head of Madrasah Mts Mamba'ul Hisan Sidayu Gresik has implemented three stages of clinical supervision. First, planning, which is done by the Head of the Madrasah to enhance the professionalism of teachers by designing what will be supervised according to the needs and requirements of the teachers, involving several senior teachers. Second, implementation, conducted by the Head of the Madrasah, which will have a positive impact on the teachers in the madrasah, as the teachers will also better understand their duties as professional educators. Third, the advantages and disadvantages of clinical supervision conducted by the Head of the Madrasah in enhancing teacher professionalism include several disadvantages such as time constraints, infrastructure, lack of teachers in general subjects, and economic factors. The advantages include the Head of the Madrasah holding teacher council meetings, the implementation of madrasah regulations, and for teachers with economic difficulties, the Head of the Madrasah provides additional hours so that they can focus on their duties as educators.